Physico-chemical Analysis of Wetlands in Madhubani District, Bihar - Anamika (Asian Journal of Chemistry, 2010)
In this paper, physico-chemical parameters of wetland water analysis were carried out from various sampling station of Madhubani District, Bihar during the rainy and winter season for the year 2003-2005.